Pemberdayaan Ekonomi Perempuan melalui Pelatihan Kewirausahaan Pembuatan Batik Desa di Desa Sendang Senori - Ika Nazilatur Rosida; Izzatul Ilmiyah; Husnama Patih (STAI Senori Tuban, 2025)
The Community Service Team of the Islamic Economics Study Program of the Senori Islamic College of Tuban employs this community service. The stages carried out include: planning, survey, preparation, implementation, monitoring, and evaluating. Community service aims to realize the goals of the national economic and welfare system to be evenly distributed, just, and sustainable through women's participation in women's empowerment activities in MSME batik-making activities in Sendang Senori Village, Tuban. The approach used is Asset Based on Community Development (ABCD), participants are directly involved in discussions and batik-making entrepreneurial activities. Data analysis used in this study is through data collection, and reduction, then the data is presented in the form of a report and conclusions are drawn. The data validation technique used is the primary and secondary data triangulation approach. The results of community service show that women's batik-making entrepreneurial activities in Sendang Village can increase family welfare and income, but further assistance is also needed regarding financial management, marketing, and product distribution.